DETERMINANTS OF INNOVATIVE WORK BEHAVIOR MEDIATED BY PSYCHOLOGICAL CAPITAL IN OIL AND GAS INDUSTRY EMPLOYEES - Muhammad Syahrul Ramadhan; Justine Tanuwijaya (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: This study aims to examine the effects of authentic leadership, psychological empowerment, and empowering leadership on innovative work behavior (IWB) among oil and gas employees in the North Sumatra (Sumbagut) region, with psychological capital mediating the relationship. Given the complex operational demands of the oil and gas industry—including expectations for efficiency, transparent governance, and sustainable innovation—fostering innovative work behavior among employees has become a strategic priority for organizational competitiveness and resilience.Methods: This study employs a quantitative descriptive methodology using an online survey (Google Forms) administered to 398 oil and gas employees from Pertamina, Pema Global Energy (PGE), and Medco Energy in the Sumbagut region. Data were collected on a cross-sectional basis and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) through SmartPLS version 3.0.Results: The findings indicate that authentic leadership does not have a direct positive effect on IWB, but positively and significantly influences psychological capital. Psychological empowerment and empowering leadership both exert positive and significant effects on IWB and psychological capital. Psychological capital is the strongest direct predictor of IWB and significantly mediates the effects of authentic leadership, psychological empowerment, and empowering leadership on IWB, confirming its central role as a psychological mechanism that translates leadership and empowerment into innovative employee behavior.Conclusion: This study offers a practical contribution to human resource management in the oil and gas industry by demonstrating that strengthening employees' psychological capital—through authentic and empowering leadership practices and psychological empowerment—is a key strategic lever for fostering innovative work behavior. Organizations are encouraged to invest in integrated leadership development and psychological capital-building programs to sustain innovation and long-term organizational performance. Keywords: authentic leadership, psychological empowerment, empowering leadership, psychological capital, innovative work behavior, oil and gas industry.